PENAFSIRAN ZAITUNAH SUBHAN DAN AMINAH WADUD TENTANG KEBEBASAN PEREMPUAN - Diana Khotibi (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2020)
A Discourse on gender is still a controversial issue today. The emergence of various inequalities in society as well as majority injustice occurs in women. The differences in roles between men and women also characterize the culture in society. The role of women is considered limited in the domestic realm, taking care of their children and husbands, while men are not limited. Religion is accused of being one of the causes for the differences between men and women. Therefore this thesis focuses on: (1) How do Amina Wadud and Zaitunah Subhan interpret the verses on women's freedom? (2) What are the similarities and differences in the interpretations of Amina Wadud and Zaitunah Subhan? This study uses a qualitative method with library research techniques or library research, which collects a variety of literature such as books, journals, theses, and theses that are in accordance with the topic of discussion. The results of this study include (1) interpreting the pronunciation of qawwamun in QS. al-Nisā: 34 Amina, interpreting as a leader. By setting two conditions, men have advantages over women. Second, provide for his wife with his own assets. While the meaning of the verse is to imply the functional relationship between men and women. Meanwhile, Zaitunah interprets the pronunciation of qawwāmūn as protector, or person in charge. Regarding nuzhūz, Amina interpreted it as a hormonal disorder, while oliveah interpreted nuzhūz as defiance related to the relationship between humans and their gods. Regarding the progress of women in the public domain, Amina and Zaitunah agree that women should be given the same opportunity to develop themselves. Biological differences according to the two are not reasons in limiting women's movement space. (2) in interpreting the verses Amina and Zaitunah use different methods. Amina Wadud used her hermeneutic method while Zaitunah Subhan used the maud}ū'ī(thematic) method